Selective Effects of the Host Matrix in Hydrogenated InGaAsN Alloys: Toward an Integrated Matrix/Defect Engineering Paradigm. (22nd October 2021) - Filippone, Francesco; Younis, Saeed; Mattioli, Giuseppe; Felici, Marco; Blundo, Elena; Polimeni, Antonio; Pettinari, Giorgio; Giubertoni, Damiano; Sterzer, Eduard; Volz, Kerstin; Fekete, Dan; Kapon, Eli; et al.
Abstract: In dilute nitride In y Ga1− y As1− x N x alloys, a spatially controlled tuning of the energy gap can be realized by combining the introduction of N atoms—inducing a significant reduction of this parameter—with that of hydrogen atoms, which neutralize the effect of N. In these alloys, hydrogen forms N–H complexes in both Ga‐rich and In‐rich N environments. Here, photoluminescence measurements and thermal annealing treatments show that, surprisingly, N neutralization by H is significantly inhibited when the number of In‐N bonds increases. Density functional theory calculations account for this result and reveal an original, physical phenomenon: only in the In‐rich N environment, the In y Ga1− y As host matrix exerts a selective action on the N–H complexes by hindering the formation of the complexes more effective in the N passivation. This thoroughly overturns the usual perspective of defect‐engineering by proposing a novel paradigm where a major role pertains to the defect‐surrounding matrix. Abstract : A theoretical model explains some experimental results in hydrogenated InGaAsN alloys by revealing a novel phenomenon. The stiffness of the N local environment governs the preference for which hydrogen structures form, thus inducing an important limitation on the actual defects production as the alloy composition is changed. This leads to a new strategy for tuning defect structures with desired properties.